Teaching-Learning Process And ICT Tools- A Review - Muhammad Hafeez (Indonesian Journal of Basic Education, 2021)
The 21st century is also called the digital age. Various information and communication technological tools are available to increase the efficacy of teaching and learning process. A review study has been conducted to review the modern information and communication technological (ICT) tools and application of these ICT tools in teaching-learning process. The review of literature indicated that various ICT tools significantly improves the teaching-learning process. So, it is essential to apply the ICT tools in teaching-learning process to achieve the desired goals.